Channel Estimation Techniques for MIMO-OFDM Systems over Frequency Selective Fading Channels - Seda ÜSTÜN ERCAN (International Journal of Applied Methods in Electronics and Computers, 2016)
Wireless channel is very complex because of  both frequency and time selectivity. In order to overcome the adverse effects of multipath fading in mobile communication channels, channel estimation must be performed.  There are three kinds of channel estimation methods: pilot based, blind and semi-blind. In pilot based channel estimation, some of data symbols are used to estimate channel. In blind channel estimation statistical properties of channel are used. In semi-blind channel estimation information from both data symbols and statistical properties is utilized. In this study, pilot based and semi-blind channel estimation are used to estimate the channels with various frequency selectivity in multiple input multiple output-orthogonal frequency division multiplexing (MIMO-OFDM) systems. Semi-blind channel estimation is done by using independent component analysis (ICA). Simulation results show that if the frequency selectivity of the channel is high, semi-blind channel estimation technique can be used instead of pilot based channel estimation. Thus with a using a small number of pilot bits, more data can be used in the MIMO systems.